Pengaruh Literasi Pajak dan Transformasi Digital Terhadap Kepatuhan Pajak - Abraham, Stenly; Waty, Lenita; Sudjiman, Lorina Suregar (ANALISIS, 2026)
This study explores the relationship between taxpayer compliance, tax literacy, and digital transformation. In this study, 60 respondents at the Pratama Cimahi Tax Office, Bandung, West Java, were given a questionnaire to collect data. Data were analyzed using PLS-SEM. The results of the outer model test indicate that all constructs have met the validity and reliability criteria. The inner model test shows that Tax Literacy has a positive and significant effect on Tax Compliance with a coefficient value of 0.563 and a p-value of 0.000, and Digital Transformation has a positive and significant effect with a coefficient value of 0.345 and a p-value of 0.002. The R-Square value of 0.697 indicates that the two independent variables are able to explain 69.7% of the variation in Tax Compliance. Thus, increasing tax literacy and optimizing digital transformation play an important role in improving taxpayer compliance.